Arts Integration and Culturally Sustaining Pedagogy: Supporting Bi/Multilingual High School Learners in Biology - Aghasafari, Sahar; Bivins, Kelli; Nordgren, Brendan (Journal of Interdisciplinary Studies in Education, 2021)
There has been a dramatic increase in the number of multilingual and multicultural students in U.S. schools. Because of high-stakes testing and English-only mandates, instructional practices, and curricula in most urban school districts neglect the cultural and linguistic interests of their diverse student populations. In this interpretive study, we use exploratory case study methods to demonstrate how Culturally Sustaining Pedagogy (CSP) and Arts Integration (including drawing and graphic story) can support the learning of ten students who speak English as their second language. This article introduces research activities supporting the use of culturally sustaining pedagogy and arts in a biology unit (the role of selection population) in communication skills class, particularly as it relates to bilingual and multilingual youth.